Detection of internal flaws in structural concrete elements by Impact-Echo technique - Bhaskar, S.; Wiggenhauser, H.; Srinivasan, P.; Murthy, S. G. N.; Ravisankar, K.; Iyer, Nagesh R.; Lakshmanan, N. (Journal of Structural Engineering, 2025)
This paper explains the application of Impact-Echo (IE) for the detection of flaws in structural concrete elements. The main objective of the paper is to detect the internal flaws such as cracks, voids, honeycombs etc. that cannot be observed by visual inspection. Studies have been carried out using a modified ‘DOCtor’ impact-echo system on a specially constructed NDT test specimen. The test specimen is designed and constructed at Structural Engineering Research Centre (SERC), Chennai, exclusively for the data generation and validation of different NDT techniques. Impact data is generated in a manual scanning mode. An average of two impacts has been taken at each point along the grid line. Impacts have been repeated in order to ensure repeatable or reproducible time domain waveforms. The waveforms have been recorded and the resulting frequency spectra have been generated by using Fourier Transformation Technique (FFT). Line (B-scan) and area (C-scan) scan images are made use of in analysing the impact data. It is observed from the analysis, that the impact-echo technique provides useful and reliable information in detecting the thickness and internal flaws such as cracks, voids etc.